2024
DOI: 10.3390/ani14020197
|View full text |Cite
|
Sign up to set email alerts
|

Breed-Specific Skull Morphology Reveals Insights into Canine Optic Chiasm Positioning and Orbital Structure through 3D CT Scan Analysis

Yoichiro Ichikawa,
Nobuyuki Kanemaki,
Kazutaka Kanai

Abstract: This study’s CT scan-based morphometric analysis of 50 adult dogs explored the relationship between skull shape variations (determined by the skull index, SI), optic chiasm, optic canals, and orbital shape. Dogs were classified as brachycephalic (SI ≥ 59), mesocephalic (SI ≥ 51 but <59), and dolichocephalic (SI < 51). No significant age or weight differences were observed. Skull lengths (brachycephalic: 11.39 ± 1.76 cm, mesocephalic: 15.00 ± 2.96 cm, dolichocephalic: 17.96 ± 3.44 cm) and facial lengths (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…The results of the study show that the OC in Holstein cow is morphologically similar to humans and morphometrically higher than humans. Ichikawa et al [22] reported that the angle between the optic chiasma and the right-left lacrimal-zygomatic joint was 93.74° in brachycephalic dogs, 67.87° in mesocephalic dogs, and 61.05° in dolichocephalic dogs. In humans, Ten et al [47] reported the angle between OC and median plane as 39.3°, Berlis et al [4] 39.1°, Cheng et al, [7] 45.3° (right), 44.2° (left), Zhang et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the study show that the OC in Holstein cow is morphologically similar to humans and morphometrically higher than humans. Ichikawa et al [22] reported that the angle between the optic chiasma and the right-left lacrimal-zygomatic joint was 93.74° in brachycephalic dogs, 67.87° in mesocephalic dogs, and 61.05° in dolichocephalic dogs. In humans, Ten et al [47] reported the angle between OC and median plane as 39.3°, Berlis et al [4] 39.1°, Cheng et al, [7] 45.3° (right), 44.2° (left), Zhang et al…”
Section: Discussionmentioning
confidence: 99%
“…The area of JF was determined in the dry skull of bison, macaque, dog, fox and rat [51], and the area of HC was determined in the same species and rabbit [50]. Using CT images, the localization of the chiasmatic sulcus (sulcus chiasmatis), its angle with some bone points [22], and the volume of the JF were determined in the dog [43], and the diameter of the trigeminal nerve canal and OF and the distances between the foramina were measured in the rabbit [20].…”
Section: Introductionmentioning
confidence: 99%